Zimbabwe : Spatial Integration in Zimbabwean Product Markets - World Bank (World Bank, Washington, DC, 2016)
The purpose of this policy note is to provide evidence on the level of integration between Zimbabwe’s domestic markets for grain and staple foods. Efficient and integrated agricultural markets are an important vehicle for growth and poverty reduction. The note determines whether Zimbabwe’s provincial markets are integrated and explores the determinants of market integration. It provides estimates of the speed of adjustment between markets pairs. The analysis investigates the extent to which distances and demand for the products determine market integration. The paper concludes with a discussion of other structural or policy related factors that affect integration and efficiency of domestic markets.